Comparing the findings of clinical examination versus magnetic resonance imaging for the diagnosis of ligamentous injuries of knee in rural area - Vishavadia, Pratik A.; Herode, Prafulla G.; Somani, Ashish M.; Reddy, Ashok V. (International Journal of Research in Orthopaedics, 2022)
Background: The knee is a complex synovial joint allowing flexion, extension, anteroposterior gliding and internal-external rotation. The major articular surfaces are the medial and lateral condyles of the femur and patellar surface. The aim of the study was to compare the findings of clinical examination versus magnetic resonance imaging (MRI) for the diagnosis of ligamentous injuries of knee in rural area. Methods: Present study was an observational study carried out at rural medical college under orthopaedic department. All patients coming with ligamentous injury to orthopaedic department were studied. Thus such 50 cases were studied. All cases were referred to radiology department for MRI of knee. MRI reports and clinical reports were compared and analysis was done. Cases contraindicated for MRI examination were excluded from study. General demoghraphic history, clinical presentation and MRI reports were recorded. All data was compiled in Microsoft excel and analysed using OpenEPi 2.3.1. Results: Mean age was 46.4±11.2 years. Majority were males 70% and 30% were females. Swelling 62% was most commonly seen followed by knee pain. Majority 58% cases had grade 3 tear on MRI, followed by 36% had grade II and only 6% had grade I. Conclusions: MRI is an excellent, non-invasive, radiation free imaging modality with multilane capabilities and excellent soft tissue delineation. It can accurately detect, localize and characterize various internal derangements of the knee joint and help in arriving at a correct anatomical diagnosis thereby guiding further management of the patient.